#TITLE_ALTERNATIVE# - HAFIDZ (NIM 10104031), MOHAMMAD
A longitudinal flow of viscous fluid around an array of parallel pipe can be founded everywhere for instance in industry or natural science. Some variables which observed are the longitudinal velocity and the flow rate of the fluid. In this system, the cross-section of the pipe affects the flow rate. In this final project, the flow around a non-circular cross-section pipe studied analytically by means of boundary perturbation method. The distribution of fluid velocity is expanded in term of small parameter up to and including the third order. The flow rates of the pipe with various cross-section area are then compared to decide which one gives a maximum value.